Evaluación de la fermentación y estabilización de una bebida de chonta (Bactris gasipaes) con preparado enzimático. - Villacís Acosta, Daysi Marisol (2021)
ABSTRACT This research objective was to evaluate the addition of an enzyme preparation in which a 1:1 dilution of chontaduro masate and water as solvent was made, where the concentrations of the enzymes α-amylase and β-amylase were calculated, which was added to the solution, it was evaluated during the time of 72 hours, where the treatments were at room temperature, for the chonta drink fermentation, the enzymatic preparation was used as a substitute for chewing, since, by hand, this Chicha is fermented thanks to the amylase contained in people's saliva. For which a completely randomized block design (DBCA) was performed, with factorial arrangement AxB (3x2), with 2 repetitions, obtaining a total of 18 treatments, the factors evaluated were: factor A (concentration of enzyme preparation) and factor B (activation time), 6 treatments were formulated as follows: t1 (0.05% - 40 min), t2 (0.05% -80 min), t3 (0.10% - 40 min), t4 (0.10% - 80 min), t5 (0.15% - 40 min), t6 (0.15% - 80 min) and the fermentation process was evaluated according to the following response variables: pH, soluble solids and acidity; data that were taken every 24 hours, from 0 hours to 72 hours. The statistical analysis of the data obtained was carried out using the Infostat software, with which the best treatment t6 a3b2 (0.15% - 0.80 min) was determined, presenting a pH of 4.86 and titratable acidity of 0.44 %, Brix degrees of 8.47, for which it was determined as the best treatment in the fermentation process. After analyzing the best treatment in the fermentation process of the chonta drink (Bactris gasipaes), the stability of the best treatment was evaluated by applying the same fermentation preparation methodology until the stabilization process was reached, where the stabilizers xanthan gum and carboxymethylcellulose. For which a completely randomized block design (DBCA) was carried out, under a factorial arrangement AxBxC (2x2x2), with two repetitions, obtaining a total of 16 treatments, where the factors were: factor A (type of stabilizer), factor B (percentage of stabilizer), factor C (storage temperature), 8 treatments were formulated as follows: t1 (xanthan gum - 0.30% - refrigeration), t2 (xanthan gum - 0.15% - refrigeration), t3 (xanthan gum - 0.30% - room temperature), t4 (xanthan gum - 0.15% - room temperature), t5 (CMC - 0.30% - refrigeration), t6 (CMC - 0.15% - refrigeration), t7 (CMC - 0.30% - ambient temperature), t8 (CMC - 0.15% - ambient temperature) and the stabilization process was evaluated according to the following response variables: syneresis, density and viscosity, the data were taken every 24 hours for three days, using the statistical program Infostat, through which it was possible to determine that the best treatment was t2 a1b2c1 (xanthan gum a - 0.15% - refrigeration), presenting a syneresis of 0%, a density of 1.01 and a viscosity of 0.38 poises, for which the appropriate treatment was determined in comparison to the other treatments.